COVID-19 in Lifespan: Psychological Impact between Young and Older Adults in Argentina - García, Matías Jonás (2022)
Abstract: The coronavirus pandemic has had a serious and worldwide impact. The increase in psychopathological symptomatology has affected people regardless of their age but has been observed mainly in the elderly population due to the characteristics of the virus. This study aimed to analyze and compare the psychological impact, as measured by the presence of depressive and anxiety symptoms, in a group of young and older adults at three-time points during the pandemic. Virtual surveys were used to measure participants’ symptomatology and collect socio-demographic information. The results showed a significant increase in anxiety and depression in the general population. However, when comparing the two groups, statistical differences were observed. Younger adults showed higher mean anxiety and depression than older adults, which was sustained across the three times for both groups. Nevertheless, the increase in depressive symptomatology slows in young people between the second and third waves, while it continues to increase in older adults. Those results are a contribution to the study of individual differences in the psychological impact of the COVID-19 pandemic.